Main determinants of new services development in ICT firms: A theoretical approach - Emerson Mainardes; Carlos Mattos; Helena Alves (The International Journal of Management Science and Information Technology (IJMSIT), 2016)
Although there are several studies about innovation and New Services Development (NSD), investigations about innovation in ICT firms are rare, in particular identifying the attributes that generate NSD in ICT firms in a single study. Thus, the objective of this research was to identify the attributes that generate new services in ICT firms, and from these, to develop an explanatory diagram of this phenomenon. The available literature indicates that marketing attributes (market research, promotion strategy, price policy, current product portfolio, selling strategy and selling channel), environmental attributes (legal and normative environment, technological change, competitors' actions, customers' actions and providers' actions) and attributes of organizational structure (technological configuration, skills and abilities, know-how, internal processes, interdepartmental communication, R&D, production pace and decision making pace) influence NSD in ICT firms. The main academic contribution of this research is thus the proposal of an initial explanatory model of NSD in ICT firms.
Keywords: 650; New Services Development (NSD); Information and Communication Technology (ICT); Services Innovation